The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.56093/ijans.v90i12.113199
|View full text |Cite
|
Sign up to set email alerts
|

Influence of in ovo threonine on growth performance, immunocompetence and carcass characteristics in broiler chickens

Abstract: The experiment was conducted to investigate the effect of in ovo threonine (Thr) injection on 18th embryonation day at the broad end of the egg using 24G needle on growth performance, organs development, immunocompetence and carcass yield in broiler chickens. Fertile eggs (n=500) were randomly distributed to 5 groups, viz. (i) uninjected control, sham control (0.5 mL sterile water), Thr @15 mg/egg, Thr @30 mg/egg, and Thr @45 mg/egg. Hatchability was better in chicks treated with 45 mg Thr/egg compared to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(74 reference statements)
1
2
0
Order By: Relevance
“…When compared to the control group, the reduction was more pronounced for T3 and T5, with 19% reductions, followed by T4 with 10% reductions. This finding was similar to that of Akshat et al [24], who discovered that eggs injected with vitamin B2 had lower hatchability than un-injected control eggs. Also, adding vitamin B6 in the early embryonic stage resulted in embryonic growth retardation, resulting in death and, eventually, poor hatchability .On the other hand, Ibrahim et al [25], discovered that in ovo feeding on the 18th day of incubation had no effect on hatchability .However, Uni & Ferket [26] discovered that in ovo feeding on the 18 th day of incubation had no effect on hatchability.…”
Section: Hatchability and Production Performancesupporting
confidence: 91%
See 2 more Smart Citations
“…When compared to the control group, the reduction was more pronounced for T3 and T5, with 19% reductions, followed by T4 with 10% reductions. This finding was similar to that of Akshat et al [24], who discovered that eggs injected with vitamin B2 had lower hatchability than un-injected control eggs. Also, adding vitamin B6 in the early embryonic stage resulted in embryonic growth retardation, resulting in death and, eventually, poor hatchability .On the other hand, Ibrahim et al [25], discovered that in ovo feeding on the 18th day of incubation had no effect on hatchability .However, Uni & Ferket [26] discovered that in ovo feeding on the 18 th day of incubation had no effect on hatchability.…”
Section: Hatchability and Production Performancesupporting
confidence: 91%
“…This result was in agreement with those of Babak et al [29] ,They found that broilers' TP and albumin levels increased significantly (P<0.05) when vitamin B12 was administered into eggs in ovo on day 42 after hatching. The blood protein level was higher (P<0.05)following vitamin B2 and B6 treatment, according to Akshat et al [24], who reported the same outcome. T1: control group, T2: eggs were injected with 0.5 mL distilled water, T3: eggs were injected with 100 mg/egg vitamin Bcx, T4: eggs were injected with 200 mg/egg vitamin Bcx, and T5: eggs were injected with 300 mg/egg vitamin Bcx.…”
Section: Blood Metabolites and Thyroid Hormones Levelmentioning
confidence: 70%
See 1 more Smart Citation